URGENSI KEPEMILIKAN AKTA CERAI BAGI MASYARAKAT BATU SONDAT DALAM MENJAGA KETAHANAN KELUARGA DI KECAMATAN BATAHAN KABUPATEN MANDAILING NATAL - Rita Defriza (Jurnal Keislaman, 2022)
Families that are not harmonious and there are disputes that lead to divorce, this has a negative impact on the resilience of families in society. Divorce that is carried out outside the court or without registering the divorce at the Court, be it the District Court or the Religious Court, results in losses for family elements, both the wife and husband who are divorced, and the children as a result of the divorce and the assets acquired during the marriage. This study aims to understand the level of understanding or knowledge of the people in Batu Sondat village in dealing with divorce and ownership of divorce papers. The legal attitude and legal behavior of the community in Batu Sondat village in the ownership of the divorce certificate, as well as the efforts made in the ownership of the divorce certificate and the ownership of the divorce certificate on family resilience in the village of Batu Sondat. The method in this research uses descriptive analysis, namely research that focuses on the results of observations and interviews with various informants appointed by the researcher. The subjects in this study were the Batu Sondat community, the research results obtained were that many people did not know about divorce procedures by registering divorces at the Court, whether it was the registration of divorces at the District Court and the Religious Court, the court's distance from the domicile area and the costs and time involved. It will take a long time if their divorce is carried out in court, in the sense that many people are still not abiding by the law. The conclusion is the importance of developing and raising awareness of the law for the community to own divorce papers, the importance of the law conveying to the community that divorce must be carried out and registered in court and the consequences resulting from divorce. Divorce that occurs outside the court or is not registered in court has a negative impact and a very non-negative impact on both the children, wife and husband who is divorced, and assets acquired during the marriage. The importance of increasing the law against the community so that people are aware of and obey the law and do not violate the law itself.